Homecoming - Kelly, Cathy (Harper London, 2012)
Eleanor Levine left Ireland with just a suitcase and her mother's recipe book. A lifetime later, she has returned from New York to Dublin's beautiful Golden Square full of hard-won wisdom. As she watches life unfold from her window, whe is drawn into the lives of the women who live in the square -- back cover